Ca/Al and Mg/Al LDH Supported on Biochars As Effective Adsorbent and Highly Regeneration Ability for Phenol Removal from Aqueous Solution - Erni Salasia Fitri; Try Nanda Yunita; Risfidian Mohadi; Aldes Lesbani (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2023)
This research conducted a composite of Ca/Al and Mg/Al Layered double hydroxide with Biochar material using co-precipitation method. Characterization results were carried out with various analyses including XRD, FT-IR, and BET. The results of XRD analysis on Ca/Al-BC showed peaks at 10-11° and 22°, while the Mg/Al-BC material showed peaks at 11. 41° (003), 22. 95° (002), 34. 05° (012) and 60.2° (116). The FT-IR analysis showed that Ca/Al and Mg/Al LDH materials composited with Biochar have functional groups of -OH, nitrate ions, C=O, C-H, C-O, and M-O. BET analysis results show an increase in surface area in Ca/Al and Mg/Al LDH materials after composite with biochar from 29.333 m2/g to 158.291 m2/g in Mg/Al-BC, while in Mg/Al-BC there is an increase from 23.150 m2/g to 111.404 m2/g. The Ca/Al-BC and Mg/Al-BC composite materials have better stability than Ca/Al and Mg/Al LDH materials that can be used up to the fifth cycle. Hydrogen bonding and π-π interaction between the adsorbent and the aromatic ring on phenol can affect the adsorption process.